2023
DOI: 10.3390/su151612489
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Remote Work on the Work Stress of Workers in the Context of the COVID-19 Pandemic: A Systematic Review

Roberto Carlos Dávila Morán

Abstract: The objective of this study was to explore the research carried out and the existing scientific information on remote work and its influence on the work stress of workers in the context of the COVID-19 pandemic. The specific objectives were as follows: to determine the factors of remote work that influence the work stress of workers in the context of the COVID-19 pandemic and to analyze the findings obtained in the study (which was achieved by referring to the influence of remote work and the labor stress of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…This study indicated that concerns are grouped under the dimensions of perceived employee barrier, intense technology barrier, working life and work-life balance. Data and technology issues [72], effective communication [67], social interactions and isolation [71], work-related stress [65,68], overworking [67,70,72], family life [74], and video conference fatigue [75,76]-all of which are identified in the literature as cons of working remotely-overlap with the concerns about online meeting tools in this study. In a study [38] investigating the impact of social isolation, technostress, and personality on users' acceptance of online meeting platforms, the similarity of technostress to the intense technology barrier in our study, and the proximity of the social isolation variable to the adaptation to change variable in our study are significant.…”
Section: Theoretical Contributionsmentioning
confidence: 82%
See 1 more Smart Citation
“…This study indicated that concerns are grouped under the dimensions of perceived employee barrier, intense technology barrier, working life and work-life balance. Data and technology issues [72], effective communication [67], social interactions and isolation [71], work-related stress [65,68], overworking [67,70,72], family life [74], and video conference fatigue [75,76]-all of which are identified in the literature as cons of working remotely-overlap with the concerns about online meeting tools in this study. In a study [38] investigating the impact of social isolation, technostress, and personality on users' acceptance of online meeting platforms, the similarity of technostress to the intense technology barrier in our study, and the proximity of the social isolation variable to the adaptation to change variable in our study are significant.…”
Section: Theoretical Contributionsmentioning
confidence: 82%
“…The first step in the quantitative instrument development process was the generation of an item pool. In order to select the best possible items, the items obtained as a result of the coding performed in the qualitative research and the item styles of the technology acceptance models in the literature were used [65][66][67][68][69][70][71][72][73][74][75][76]. At the end of this step, a pool of 66 items was generated.…”
Section: Quantitative Instrument Development and Quantitative Data Ac...mentioning
confidence: 99%